2018
DOI: 10.5812/iranjradiol.67211
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole Induced Encephalopathy: A Case Report Showing Devastating Course on Consecutive MR Imaging

Abstract: Metronidazole-induced encephalopathy is a rare neurologic adverse effect of an antibiotic drug 'metronidazole'. Although it is usually reversible with immediate cessation of the drug, it can also be fatal when used continuously. Here, we present a 72-yearold female who was on metronidazole for a total of 46 consecutive days. Her initial MRI on the 22nd day of medication use revealed a typical involvement of the cerebellar dentate nuclei, corpus callosum splenium, and periaqueductal midbrain, suggesting metroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Resolution of clinical signs and MRI lesions in most patients between 3 and 16 weeks after drug discontinuation has been reported in humans. 5 In conclusion, metronidazole neurotoxicity is a cause of cerebellar and central vestibular deficits in dogs. Patient history, including previous or current gastrointestinal conditions and metronidazole administration, should alert the clinician to the possibility of metronidazole toxicosis.…”
Section: Commentsmentioning
confidence: 91%
See 2 more Smart Citations
“…Resolution of clinical signs and MRI lesions in most patients between 3 and 16 weeks after drug discontinuation has been reported in humans. 5 In conclusion, metronidazole neurotoxicity is a cause of cerebellar and central vestibular deficits in dogs. Patient history, including previous or current gastrointestinal conditions and metronidazole administration, should alert the clinician to the possibility of metronidazole toxicosis.…”
Section: Commentsmentioning
confidence: 91%
“…4 Consistent with the MRI features for the dog of the present report, the most characteristic change in people with metronidazole neurotoxicity is symmetric hyperintensity of dentate nucleus on T2-weighted or FLAIR images, though it can also affect other intracranial sites, such as the midbrain, pons, medulla, and splenium of corpus callosum. 5,6 Tauro et al 3 reported non-contrast-enhancing, symmetric T2 and FLAIR hyperintensity of the dentate nuclei in a dog with metronidazole neurotoxicity. It is important to note that in that study, 3 only 1 of the 19 dogs with clinically suspected metronidazole neurotoxicity that had MRI performed showed changes to the dentate nuclei, underscoring the possibility of premature exclusion of a reversible condition based on normal imaging findings alone.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation